2015
DOI: 10.1108/mhrj-04-2014-0014
|View full text |Cite
|
Sign up to set email alerts
|

Effects of employment as a peer support worker on personal recovery: a review of qualitative evidence

Abstract: Purpose -The purpose of this paper is to systematically identify, appraise and synthesise qualitative research into how working as a peer support worker (PSW) affects personal recovery. Design/methodology/approach -Ten articles were identified through a systematic search of seven databases, grey literature, reference lists, citations and contact with authors in the field. Identified articles were critically appraised and their results synthesised using metaethnography. Findings -There is potential to significa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
87
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 33 publications
(89 citation statements)
references
References 37 publications
(62 reference statements)
2
87
0
Order By: Relevance
“…Our findings indicate that peer workers should not be automatically restricted from engaging in such challenging situations, but rather have the opportunity to explore these situations as part of a learning process. Having this opportunity can enable peer workers to increase their self‐care behaviour and to enhance their knowledge about mental health and recovery (Bailie & Tickle ; Moran et al . ).…”
Section: Discussionmentioning
confidence: 99%
“…Our findings indicate that peer workers should not be automatically restricted from engaging in such challenging situations, but rather have the opportunity to explore these situations as part of a learning process. Having this opportunity can enable peer workers to increase their self‐care behaviour and to enhance their knowledge about mental health and recovery (Bailie & Tickle ; Moran et al . ).…”
Section: Discussionmentioning
confidence: 99%
“…The role is complex, as peer support workers hold multiple identities, which must be negotiated both by them (Dyble et al, 2014) and those they support (Bailie et al, 2016). Evidence suggests employment as a peer support worker can be both facilitative and detrimental to personal recovery, although the quality and extent of research is limited (Bailie and Tickle, 2015). However, a systematic review of peer-support for individuals with 'severe mental illnesss' reported a moderate degree of effectiveness, including improvements in service-user empowerment, self-advocacy, hopefulness, engagement, and relationships with providers, as well as reduced inpatient admissions (Chinman et al, 2014).…”
Section: Originality / Valuementioning
confidence: 99%
“…Additional criteria evaluated the method and analysis and therefore enabled a broader review of the evidence in comparison with the original CASP (2013b). The framework outlines 14 criteria for appraising each of the review papers, applying a scoring system defined by Bailie and Tickle (2015) as follows: '2' if definitely met, '1' if unclear or ambiguous, and '0' if not met. Studies were independently ranked by the first author and second author, and a mean score was calculated.…”
Section: Number Of Duplicates Removedmentioning
confidence: 99%